Sensitization mechanism of metal oxide nanocluster resists with carboxylic acid ligands. (1st August 2022) - Otsuka, Tomoe; Muroya, Yusa; Ikeda, Takuya; Komuro, Yoshitaka; Kawana, Daisuke; Kozawa, Takahiro
Abstract: Metal oxide nanocluster resists are a promising candidate for enabling the high-volume production of semiconductor devices with high-numerical-aperture extreme ultraviolet exposure tools. In this study, the sensitization mechanism of metal oxide nanocluster resists was investigated by focusing on the radiation-induced reactions of carboxylic acid ligands. Radiolytic products in various solutions of unsaturated carboxylic acids, aromatic carboxylic acids, and saturated carboxylic acids were analyzed by electrospray ionization mass spectrometry, high-performance liquid chromatography, and dynamic light scattering. The conditions of the solutions were selected to control reaction paths of intermediates. The major reaction paths induced by ionizing radiation were clarified. The obtained results suggest that the generation of bridging ligands is essential to the sensitization of metal oxide nanocluster resists. Both low-energy electrons and radical cations can trigger dimerization. The diffusion of small radicals should be suppressed to prevent dimerization at undesired places.